Fall-risk-increasing drugs in older patients: the role of guidelines and GP-centred health care in Germany - Laux, Gunter; Kaufmann-Kolle, Petra; Szecsenyi, Joachim; Altiner, Attila; Leutgeb, Rüdiger (Age & ageing, 2023)
Fall-Risk-Increasing Drugs (FRIDs) are a ubiquitous issue, especially for older patients. As part of a German guideline for pharmacotherapy, from 2019, a new quality indicator for this patient group was developed to measure the percentage of patients receiving FRIDs.
Online veröffentlicht am 27. Mai 2023
Gesehen am 12.12.2023